Fixed- versus adjustable-loop femoral fixation in anterior cruciate ligament surgery: Is one method clinically superior? - Yücel, Mücahid Osman; Dalaslan, Raşit Emin; Sağlam, Sönmez; Karaduman, Zekeriya Okan; Arıcan, Mehmet (The European Research Journal, 2025)
Objectives: This study aimed to compare fixed-loop and adjustable-loop femoral fixation systems in anterior cruciate ligament (ACL) reconstruction to determine whether one provides superior short-term clinical outcomes. Methods: This retrospective cohort study included 88 patients who underwent anatomic ACL reconstruction by the same surgical team at Düzce University Faculty of Medicine between January 01, 2018 and December 31, 2023. Patients were divided into two groups as those with a fixed-loop (n=39) and those with an adjustable-loop (n=49). A standard postoperative rehabilitation program was applied to all patients. Lysholm knee score, International Knee Documentation Committee (IKDC) score, Visual Analog Scale (VAS), and range of motion (ROM) were evaluated preoperatively and 6 months postoperatively as clinical evaluation parameters. Results: Both groups demonstrated significant improvement in VAS, Lysholm, and IKDC scores during the postoperative period (P0.05). Conclusions: Fixed- and adjustable-loop femoral fixation systems used in ACL reconstruction show similar performance in terms of short-term clinical outcomes. Both methods can be safely preferred; the final choice of method should be based on the surgeon's experience and patient-specific factors. Further studies evaluating long-term outcomes are needed.